Recent progress in cassava agronomy research in India - Nayar, T.V.R.; Kabeerathumma, S.; Potty, V.P.; Mohankumar, C.R. (International Center for Tropical Agriculture, 1995)
Cassava is an important crop in India, with an area of 289,000 ha and production of 5.6 million t of fresh roots in 1991. It is mainly cultivated in Kerala, Tamil Nadu, Andhra Pradesh and in the Northeastern states. A large variation in cassava consumption exists between urban and rural areas in India. About 70% of cassava production in Kerala is used for food. In Tamil Nadu, however, only 25% is used for human consumption, while the rest is used for industrial utilization, mainly for starch production. About 17% of cassava production in the country is used for animal feed. Cassava is used in industry for production of starch, sago, liquid glucose, dextrin, vitamin C, gums and high-fructose syrup. Earlier agronomy research concentrated on the development of cultural practices and soil fertility management for cassava grown in monoculture. Recently, research has focused on the development of cassava-based cropping systems, soil fertility management with emphasis on micronutrients and bio-fertilizers (especially VA-mycorrhiza), low-input technology, water management and production practices for non-traditional areas. Short-duration cassava cultivars were shown to produce higher root yields at closer spacing of 75x75 cm, while for cassava grown under coconuts a plant population of 8000/ha was found to be optimum. Under intercropping with groundnut or cowpea the paired-row cassava system performed best. In acid infertile soils in Kerala, continuous cropping of cassava with application of only NPK chemical fertilizers resulted in a depletion of Ca, Mg, Cu and Zn in the soil. From the study on interrelationships of cations the optimum doses of K, Ca and Mg were found to be 146 kg K^O, 56 kg Ca and 37 kg Mg/ha. Incorporation of ZnSO at 12.5 kg/ha increased the root yield 12%. An NPK application of 50:62:62 kg/ha was sufficient for the cassava-ground nut intercropping system if the haulms of groundnut were turned back into the soil. For cassava grown under coconut an NPK rate of 50:50:100 kg/ha gave higher net returns. For rice-cassava sequential cropping on paddy soils the P application rate to cassava could be reduced to 25 kg P O /ha. In calcareous soils of Tamil Nadu short duration cassava cultivars performed better at lower levels of NPK (75:25:75 kg/ha). Application of a liquid NPK fertilizer at the rate of 8-8-8 kg/ha was equally effective as the same rate applied in solid form. Inoculation of VA mycorrhiza (VAM) enhanced the dry matter production, root yield and uptake of P, Cu and Zn in cassava. For successful field inoculation a nursery techniquewas developed. To realize the production potential of high-yielding cassava, the application of NPK at 150:100:150 kg/ha and supplementary irrigation at an IW/CPE ratio of 1 were found necessary. In cassava-groundnut intercropping systems, supplementary irrigation during drought periods at 25 mm/week enhanced the yield of both crops. Studies on effects of subsoil moisture on cassava showed that a shallow water table (around 40 cm from the surface) depressed root yields.